Sustainable Finance in Emerging Markets : Evolution, Challenges, and Policy Priorities - Goel, Rohit; Gautam, Deepali; Natalucci, Fabio (Washington, D.C. : International Monetary Fund, 2022)
Sustainable finance has become a key focus area for global investors and policy makers. Last year proved to be a breakout year for emerging markets (EMs), with sustainable debt issuance in 2021 surging to almost USD 200 billion. This working paper, the first comprehensive study in the literature, analyzes the evoluiton of EM sustainable finance markets, including differences with advanced economies. The analysis shows how sustainable finance in EMs is growing fast not just in aggregate but importantly across many dimensions. The paper also identifies key development areas for EMs and policies to strengthen the resilience of sustainable finance markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Environment and Development; Environment and Trade; Environmental Accounts and Accounting; Environmental Equity; Sustainability